Higher Education and the Professional Job Market - Alejandro Mungaray Lagarda (Universidad Autónoma de Baja California, 2001)
The paper deals with the relationship between the professional job market and institutions of higher education, within the framework of socioeconomic globalization and regional decentralization processes. The discussion focuses on how this relationship generates flaws in the market due to the role played by higher education as an intermediary between job applicants and those offering employment and professional opportunities; and due also to the fact that higher education institutions have their own objectives, which differ from those of the market. The article states the need to acknowledge and overcome the limitations which the concentration of income imposes on Latin American students' access to this educational level and their continuance in it. The paper also stresses the need for a closer connection between academic and job practices through curricular changes and the certification of knowledge that will be useful on the job. This would allow a better correlation with the productive sector, in that it would improve the absorption of graduates.